The 1619 project eaudiobook Born on the water. - Hannah-Jones, Nikole (Listening Library, 2021)
The 1619 Project’s lyrical picture book in verse, adapted for audio, chronicles the consequences of slavery and the history of Black resistance in the United States, thoughtfully rendered by Pulitzer Prize-winning journalist Nikole Hannah-Jones and Newbery honor-winning author Renée Watson. A young student receives a family tree assignment in school, but she can only trace back three generations. Grandma gathers the whole family, and the student learns that 400 years ago, in 1619, their ancestors were stolen and brought to America by white slave traders. But before that, they had a home, a land, a language. She learns how the people said to be born on the water survived.   And the people planted dreams and hope, willed themselves to keep living, living.   And the people learned new words for love for friend for family for joy for grow for home.   With powerful verse and striking illustrations by Nikkolas Smith, Born on the Water provides a pathway for readers of all ages to reflect on the origins of American identity.